IMPACT OF NASOALVEOLAR MOLDING ON MAXILLARY ARCH DIMENSIONS AND MALOCCLUSION CHARACTERISTICS IN PEDIATRIC PATIENTS WITH CLEFT LIP AND PALATE DURING PRIMARY DENTITION - IDREES , S; ADNAN, MA; KHAN , T; KHALIL , U; HASSAN , S; SHAHID , H (Biological and Clinical Sciences Research Journal, 2023)
Unilateral complete cleft lip and palate (UCLP) are congenital disabilities when a baby's lip or mouth does not form properly during early pregnancy. This retrospective study investigated the long-term effects of passive alveolar molding (PAM) and nasoalveolar molding (NAM) on cleft width and maxillary growth parameters in children with UCLP. A retrospective study of children with UCLP was enrolled and divided into two groups: PAM and NAM. Cleft width measurements were obtained at baseline and regular intervals during the follow-up period. Maxillary growth parameters were also assessed, including arch width, dental occlusion, and facial symmetry. Data were analyzed using descriptive statistics, chi-square tests, and linear regression models. Data was collected from 52 patients according to the inclusion criteria. The NAM group consisted of 22 patients with UCLP (mean age of 3.98 ± 1.6 years) and 12 patients with BCLP mean age of 3.81 ± 1.9 years. Fourteen patients with UCLP (mean age 3.9 ± 1.9 years) and four patients with BCLP and mean age 4.4 ± 2.1 years were included in the non-NAM group. It is concluded that the results of our study suggest that passive alveolar molding (PAM) and nasoalveolar molding (NAM) have a significant impact on cleft width reduction and maxillary growth in unilateral cleft lip palate (UCLP).